PENGEMBANGAN MODUL PEMBELAJARAN MATA KULIAH TEKNOLOGI PANGAN (TP) - Yensasnidar Yensasnidar (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2017)
This research is motivated by several problems which are identified in the subject of Food Technology, namely the existing module has not facilitated the students to study individully, it has not been suitable to the theories of module development, the students are not independent and active in learning process, it is necessary to develop the learning module of Food Technology which is suitable to the standard of competency. The purpose of this research is to produce the valid, practical and effective learning module in order to be used in learning process.This reaserch was carried out by using research method and development of Research and Development (R & D) with four-D development model (4D). the steps of 4D development are Define (definition), Design (design), Develop (development) and Disseminate (Dissemination). The results of this development research are as follows; (1) learning module of food technology subject; and the aspect of module format which is stated as valid with value total 0,83%; (2) the validity of learning module in material aspectof module (valid) is 0,85%; (3) practicality of learning module that is based on lecturer’s response is stated as very practical with value total 96,9% and based on student’s respons is stated very practical with value total 84,27%; (4) the effectiveness of learning module is stated as effective in improving student learning result. Based on the findings of this study were concluded that this learning module is valid, very practical, and effective to be used as teaching material of food technology subject.